SAGE Sourcebook of Modern Biomedical Devices: Business Environments in a Global Market - DRI, Decision Resources, Inc (SAGE Publications, Incorporated, 2007)
Special Introductory offer: £725.00 Normal price: £850.00 SAVE £125.00 The Encyclopedia of Biomedical Devices includes information on over 180 types of devices in all existing therapeutic areas of application, it is unique in that it fills the existing gap. Presented in a crisp, concise style, the data on device markets are analyzed and offered in brief chapters, each dedicated to the specific biomedical device. The methodology used to analyze these data, is also presented for each device. This is a truly unique reference work, directory and guide not only for libraries and working groups, but also for researchers and graduate students working in all fields of biomedical devices, in both physical and life sciences, including departments of engineering, materials science, applied physics, chemistry and medical schools. It is also an essential tool for professionals working within the field, government organizations, funding agencies, health care providers and hospital libraries. Areas covered include: CARDIOVASCULAR DEVICES CARDIOVASCULAR - PERIPHERAL VASCULAR CARDIOVASCULAR - TRANSCATHETER EMBOLIZATION OCCLUSION CARDIOVASCULAR - VASCULAR ACCESS CARDIOVASCULAR - CARDIAC SURGERY ORTHOPEDIC DEVICES ORTHOPEDICS - TRAUMA IMPLANTS ORTHOPEDICS - SPINAL IMPLANTS ORTHOPEDICS - ORTHOPEDIC BIOMATERIALS ORTHOPEDICS - DENTAL IMPLANTS ORTHOPEDICS - OTHER ORTHOPEDICS ENDOSCOPY DEVICES UROLOGY & GYNECOLOGY DEVICES AESTHETIC DEVICES OPHTHALMIC DEVICES DIAGNOSTIC IMAGING HEALTH CARE INFORMATION TECHNOLOGY.